Does Accounting Conservatism Reduce Default Risk? Evidence from Taiwan - Kuo, Chen-Yin (International Journal of Economics and Financial Issues, 2018)
Differing from existing research focusing on the relations between default risk and equity returns, corporate governance, tax allowance, this paper investigates whether accounting conservatism (accounting conservative reporting) reduces default risk. We adopt Taiwanese high-tech and traditional industries as samples and find that for two industries, a firm that increases more accounting conservatism reduces default risk. This negative effect of accounting conservatism on default risk holds through increasing efficient investments, implying that investments serve as a channel through which conservatism has negative effects on default risk. Efficient investments more strengthen the negative effects in high-tech firms than traditional firms. For risk management practice, a manager can increase conservative accounting reporting to reduce default risk, and thereby improve a firm’s performance, attracting more investors and increasing market capitalization. A suggestion for investors is to invest a firm adopting more accounting conservatism because default risk may be lower. Keywords: Default risk; Accounting conservatism; Efficient investments JEL Classifications: C21, C23, D21, G33